Genome-wide analysis of the soybean CRK-family and transcriptional regulation by biotic stress signals triggering plant immunity. - Leonardo Delgado-Cerrone; Alfonso Alvarez; Eilyn Mena; Inés Ponce de León; Marcos Montesano (PLoS ONE, 2018)
Cysteine-rich receptor-like kinases (CRKs) are transmembrane proteins that exhibit ectodomains containing the domain of unknown function 26 (DUF26). The CRKs form a large subfamily of receptor-like kinases in plants, and their possible functions remain to be elucidated. Several lines of evidence suggest that CRKs play important roles in plant defense responses to environmental stress, including plant immunity. We performed a genome-wide analysis of CRK encoding genes in soybean (Glycine max). We found 91 GmCRKs distributed in 16 chromosomes, and identified several tandem and segmental duplications, which influenced the expansion of this gene family. According to our phylogenetic analysis, GmCRKs are grouped in four clades. Furthermore, 12% of the members exhibited GmCRKs with a duplicated bi-modular organization of the ectodomains, containing four DUF26 domains. Expression analysis of GmCRKs was performed by exploring publicly available databases, and by RT-qPCR analysis of selected genes in soybean leaves responding to biotic stress signals. GmCRKs exhibited diverse expression patterns in leaves, stems, roots, and other tissues. Some of them were highly expressed in only one type of tissue, suggesting predominant roles in specific tissues. Furthermore, several GmCRKs were induced with PAMPs, DAMPs and the pathogens Phakopsora pachyrhizi and Phytophthora sojae. Expression profiles of several GmCRKs encoding highly similar proteins exhibited antagonist modes of regulation. The results suggest a fine-tuning control of GmCRKs transcriptional regulation in response to external stimuli, including PAMPs and DAMPs. This study offers a comprehensive view of the GmCRKs family in soybean, and provides a foundation for evolutionary and functional analysis of this family of plant proteins involved in the perception of pathogens and activation of plant immunity.